Jitter-correction for IR/UV-XUV pump-probe experiments at the FLASH free-electron laser. (10th April 2017) - Savelyev, Evgeny; Boll, Rebecca; Bomme, Cédric; Schirmel, Nora; Redlin, Harald; Erk, Benjamin; Düsterer, Stefan; Müller, Erland; Höppner, Hauke; Toleikis, Sven; Müller, Jost; Kristin Czwalinna, Marie; et al.
Abstract: In pump-probe experiments employing a free-electron laser (FEL) in combination with a synchronized optical femtosecond laser, the arrival-time jitter between the FEL pulse and the optical laser pulse often severely limits the temporal resolution that can be achieved. Here, we present a pump-probe experiment on the UV-induced dissociation of 2, 6-difluoroiodobenzene (C6 H3 F2 I) molecules performed at the FLASH FEL that takes advantage of recent upgrades of the FLASH timing and synchronization system to obtain high-quality data that are not limited by the FEL arrival-time jitter. We discuss in detail the necessary data analysis steps and describe the origin of the time-dependent effects in the yields and kinetic energies of the fragment ions that we observe in the experiment.